2018
DOI: 10.1007/s00787-018-1105-4
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation difficulties in traumatized youth: a meta-analysis and conceptual review

Abstract: This article provides a quantitative and conceptual review of emotion regulation difficulties in trauma-exposed young people, and informs future directions in the field. Despite long-standing interest in the influence of emotion regulation difficulties on different internalizing and externalizing psychiatric disorders in childhood, several questions remain unresolved with respect to children and adolescents with PTSD (post-traumatic stress disorder). Meta-analytic data from adult victims suggest that emotion r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 90 publications
5
48
0
2
Order By: Relevance
“…From a clinical perspective, it is crucial to determine when negative emotions may be considered predictors, and when they can turn into symptomatic reactions. Clinical observation seems to suggest that in conditions of extreme and prolonged trauma, some negative emotions are symptomatic (Villalta et al, 2018; Khamis, 2019). In any case, this relationship needs to be further investigated in randomized studies, both longitudinally and with clinical groups of traumatized children.…”
Section: Resultsmentioning
confidence: 99%
“…From a clinical perspective, it is crucial to determine when negative emotions may be considered predictors, and when they can turn into symptomatic reactions. Clinical observation seems to suggest that in conditions of extreme and prolonged trauma, some negative emotions are symptomatic (Villalta et al, 2018; Khamis, 2019). In any case, this relationship needs to be further investigated in randomized studies, both longitudinally and with clinical groups of traumatized children.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, emotion regulation has begun to receive significant attention as a potentially important mediator between ELA and PTSD symptoms, depression, and poor physical health outcomes and therefore may be an important treatment target (Cloitre, Khan, Mackintosh, Garvert, Henn-Haase, Falvey, & Saito, 2019;Rudenstine, Espinosa, McGee, & Routhier, 2018). A meta-analysis of 41 studies found a moderately strong relationship between children and adolescents diagnosed with PTSD and difficulties with emotion regulation (Villalta, Smith, Hickin, & Stringaris, 2018). Emotion regulation has further been shown to significantly mediate the changes seen in emotion dysregulation, severity of PTSD and depression symptoms, and physical health in a sample of women enrolled in a PTSD clinical trial (Cloitre et al, 2019).…”
Section: Emotion Regulation Approachesmentioning
confidence: 99%
“…The DERS and its subscales has shown correlations with other scales measuring related aspects of emotion regulation, such as alexithymia, levels of positive and negative affect, experiential avoidance and suppression, in other populations including individuals with alcohol dependence, chronic pain, and aggression as well in psychiatric inpatient adolescents (e.g., Ghorbani et al 2017;Kökönyei et al 2014;Velotti et al 2016;Venta et al 2012). Levels of emotion regulation difficulties as measured by the DERS have also been found to be associated with different kinds of psychopathology such as personality disorders, posttraumatic stress disorders, depression and anxiety (e.g., Gratz et al 2006;Sloan et al 2017;Tull and Roemer 2007;Villalta et al 2018;Visted et al 2018). Regarding eating disorders, previous research has found associations between the DERS (total scale and all subscales) and levels of eating disorder pathology (e.g., Brockmeyer et al 2014;Burns et al 2012;Cooper et al 2014;Haynos et al 2015;Monell et al 2015;Racine and Wildes 2015), and there is also evidence of relations to specific eating disorder behaviors (e.g., Burns et al 2012;Monell et al 2018).…”
mentioning
confidence: 99%